2018
DOI: 10.1002/ghg.1762
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermal stresses on the relation between rock failure and temperature and pressure of supercritical carbon dioxide jet

Abstract: The supercritical carbon dioxide (SC‐CO2) jet is a new‐type of rock‐breaking method that effectively combines pressure impact and thermal shock. Current studies show that a carbon dioxide jet produces a larger damaged area and requires a lower threshold pressure for rock breaking compared to a water jet; however, the rock‐breaking mechanism of the SC‐CO2 jet has not been clearly explained. This study developed a heat‐fluid‐solid coupling model using ANSYS. The simulation and experimental results show good agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Chen et al (2017) showed that the main effects of liquid CO 2 phase change on coal are impact force effects and high-pressure gas quasi-static stress field effects, which produce tensile stress on coal and change the structure of the coal fissures. For compressible fluids, sudden changes in temperature occur with large pressure gradients (Li et al 2018a;Charrière et al 2010). According to Liu et al (2020a, b), thermal expansion and contraction will occur inside the rock under the effect of temperature impact.…”
Section: Scanning Electron Microscope Resultsmentioning
confidence: 99%
“…Chen et al (2017) showed that the main effects of liquid CO 2 phase change on coal are impact force effects and high-pressure gas quasi-static stress field effects, which produce tensile stress on coal and change the structure of the coal fissures. For compressible fluids, sudden changes in temperature occur with large pressure gradients (Li et al 2018a;Charrière et al 2010). According to Liu et al (2020a, b), thermal expansion and contraction will occur inside the rock under the effect of temperature impact.…”
Section: Scanning Electron Microscope Resultsmentioning
confidence: 99%
“…At present, a lot of experiments on SC-CO 2 jet rock breaking have been conducted, proving that SC-CO 2 jets have greater advantages than water jets in rock breaking [4,5,[11][12][13][14][15][16]. What is interesting about the mechanism is that a large temperature gradient and high-temperature stress can be generated under a SC-CO 2 jet, and the higher temperature stress is the main reason why the SC-CO 2 jet is superior to the water jet in rock breaking [17][18][19][20]. Nevertheless, there are few studies on the SC-CO 2 jet flow field and stress field near the critical point due to the drastic changes in density, heat capacity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, most studies have focused on new rock-breaking methods, such as jet rockbreaking, using different media and nozzle structures and have achieved various results. Li Mukun et al introduced a new rock fragmentation method that effectively combines pressure shock with thermal shock [13]. The results show that this method has a higher rock fragmentation efficiency than the water jet method.…”
Section: Introductionmentioning
confidence: 99%